Championing the green identity : uncovering the multi-faceted environmental policies. An environmental history of Singapore from 1965 to present - Yusri Rosli (Nanyang Technological University, 2022)
Singapore is well-known for its lush greeneries and is regarded as the greenest city in the world. This clean and green identity was built upon carefully constructed environmental policies. Despite the success of this green identity, most of the policies were geared to benefit Singapore as a developing nation. Hence, the paper aims to answer the research question: To what extent were these environmental policies solely for the betterment of the environment? This thesis argues that the environmental policies in Singapore was multifaceted and was carefully constructed to not only preserve the environment but also bring about other benefits that will aid a rising nation. The research paper will be structured as follows: The thesis shall present three other functions of environmental policies through three chapters. The first chapter shall present how environmental policies acted as one of the means to exercise social engineering. The second chapter shall look into how environmental policies helped distinguish Singapore from other rising nations at the time which garnered the attention of foreign investors and tourists. The third chapter shall examine how environmental policies help to uphold the current narratives of the government. The thesis shall examine environmental policies from the 1960s to the 2000s and will look into specific policies that involve interaction with society.